PENERAPAN MODEL INTEGER LINEAR PROGRAMMING DALAM OPTIMASI PENJADWALAN PERKULIAHAN SECARA OTOMATIS - Wungguli, Djihad; Nurwan, Nurwan (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Lectures scheduling is a difficult administrative task for universities. This happens because in lectures scheduling must combine the number of courses, approve the room, day and period, as well as teaching lecturers. The purpose of this article is to create an optimization model for courses scheduling using integer linear programming to minimize the level of dissatisfaction between lecturers and students. This model is applied to making a schedule in the Mathematics Study Program at Gorontalo State University. In this research, data and information collected about the scheduling of lectures as a basis for making models. There are 55 study groups scheduled in 4 rooms, 5 days and 12 time periods. Furthermore, the scheduling optimization model is made in the form of integer linear programming and is solved by LINGO 18.0 software. The result obtained from this study is a lecture schedule that is free of conflict. Lectures scheduling produced meets the requirements and requests for lecturers and students in the Mathematics Study Program. In addition, the resulting model can help the time needed to do the scheduling.